On residents' satisfaction with community health services after health care system reform in Shanghai, China, 2011 - Li Zhijian; Hou Jiale; Lu Lin; Tang Shenglan; Ma Jin (BMC, 2012)
Abstract Background Health care system reform is a major issue in many countries and therefore how to evaluate the effects of changes is incredibly important. This study measured residents' satisfaction with community health care service in Shanghai, China, and aimed to evaluate the effect of recent health care system reform. Methods Face-to-face interviews were performed with a stratified random sample of 2212 residents of the Shanghai residents using structured questionnaires. In addition, 972 valid responses were retrieved from internet contact. Controlling for sex, age, income and education, the study used logistic regression modeling to analyze factors associated with satisfaction and to explain the factors that affect the residents' satisfaction. Results Comparing current attitudes with those held at the initial implementation of the reform in this investigation, four dimensions of health care were analyzed: 1) the health insurance system; 2) essential drugs; 3) basic clinical services; and 4) public health services. Satisfaction across all dimensions improved since the reform was initiated, but differences of satisfaction level were found among most dimensions and groups. Residents currently expressed greater satisfaction with clinical service (average score=3.79, with 5 being most satisfied) and the public health/preventive services (average score=3.62); but less satisfied with the provision of essential drugs (average score=3.20) and health insurance schemes (average score=3.23). The disadvantaged groups (the elderly, the retired, those with only an elementary education, those with lower incomes) had overall poorer satisfaction levels on these four aspects of health care (P<0.01). 25.39% of the respondents thought that their financial burden had increased and 38.49% thought that drugs had become more expensive. Conclusion The respondents showed more satisfaction with the clinical services (average score=3.79) and public health services/interventions (average score=3.79); and less satisfaction with the health insurance system (average score=3.23) and the essential drug system (average score=3.20). Disadvantaged groups showed lower satisfaction levels overall relative to non-disadvantaged groups.